Kapok Seed Oil As Viscosity Index Improved - Pallawagau La Puppung (Scientific Contributions Oil and Gas, 1987)
Production, supply and development of hubricating oils for domestic use are carried out in Indonesia using domestie bate ofls and imported additives. Research on the use of kapok seed oill as a viscosity index improver for lubricating oll is as an effort for supply and development of lubricating oll additive which is produced in the country. Resuls of physical and chemical properties analysis indicate that kapok seed oil can be used Ea viscosity index improver.